Digital Breast Tomosynthesis Complements Two-Dimensional Synthetic Mammography for Secondary Examination of Breast Cancer. Issue 1 (5th November 2021) - Nakajima, Eiji; Tsunoda, Hiroko; Ookura, Mariko; Ban, Kanako; Kawaguchi, Yuko; Inagaki, Mami; Ikeda, Norihiko; Furukawa, Kinya; Ishikawa, Takashi
Objective: To compare the performance of two-dimensional synthetic mammography (SM) combined with digital breast tomosynthesis (DBT) (SM/DBT) and full-field digital mammography (FFDM) including women with DBT (FFDM/DBT) undergoing secondary examination for breast cancer. Material and Methods: Out of 186 breasts, including 52 with breast cancers; FFDM/DBT and SM/DBT findings were interpreted by four expert clinicians. Radiation doses of FFDM, SM/DBT, and FFDM/DBT were determined. Inter-rater reliabilities were analyzed between readers and between FFDM/DBT and SM/DBT by Cohen's Kappa coefficients. Diagnostic accuracy was compared between SM/DBT and FFDM/DBT by Fisher's exact tests. Two representative cancer cases were examined for differences in the interpretation between FFDM and SM. Results: A higher radiation dose was required in FFDM/DBT than in SM/DBT (median: 1.50 mGy vs. 2.95 mGy). Inter-rater reliabilities were similar between both readers and modalities. Both sensitivity and specificity were equivalent in FFDM/DBT and SM/DBT ( p = 0.874–1.00). Compared with FFDM, SM did not clearly show abnormalities with subtle margins in the two representative cancer cases. Conclusion: SM/DBT had a similar performance to FFDM/DBT in detecting breast abnormalities but requires less radiation. DBT complements SM to improve accuracy to a level equivalent to that of FFDM. Taken together, SM/DBT may be a good substitute for FFDM/DBT for the secondary examination of breast cancer.